2017
DOI: 10.1007/s11745-017-4288-4
|View full text |Cite
|
Sign up to set email alerts
|

miR‐17‐5p Regulates Differential Expression of NCOA3 in Pig Intramuscular and Subcutaneous Adipose Tissue

Abstract: Fat distribution affects economic value in pork production. Intramuscular adipose tissue (IMAT) improves meat quality, whereas subcutaneous adipose tissue (SCAT) is usually regarded as waste. In the present study, we analyzed IMAT/SCAT (I/S) ratios in each pig. Individuals selected from a population of 1200 Suhuai pigs were divided into two cohorts; those with high I/S ratios and those with low I/S ratios, and correlations between nuclear Receptor Co-activator 3 (NCOA3), a critical gene involved in regulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Rapidly evolving energy metabolism genes in BM are involved mainly in adipose deposition (such as AGPAT2, AGPAT4, AWAT1, and FABP6) and the growth and development of cardiac and skeletal muscles (such as FGFR2, FGFR4, and IGFBP4), reflecting a need to enhance the efficiency of biomass production under the nutrient-restricted feeding condition. Conversely, energy metabolism PSGs in Duroc are involved mainly in diabetic diseases, including eight PSGs playing important roles in resistance to diabetes (GAPT4, ZNF608, and BBS2) (Nishimura et al, 2001;Speliotes et al, 2010), atherosclerosis (SERPINE1) (Koch et al, 2010), insulin secretion (UCP2) (Bordone et al, 2006), and energy expenditure (GPAM, PRKCA, and NCOA3) (Han et al, 2017;Yu et al, 2017).…”
Section: Bidirectional Selection In Bm and Durocmentioning
confidence: 99%
“…Rapidly evolving energy metabolism genes in BM are involved mainly in adipose deposition (such as AGPAT2, AGPAT4, AWAT1, and FABP6) and the growth and development of cardiac and skeletal muscles (such as FGFR2, FGFR4, and IGFBP4), reflecting a need to enhance the efficiency of biomass production under the nutrient-restricted feeding condition. Conversely, energy metabolism PSGs in Duroc are involved mainly in diabetic diseases, including eight PSGs playing important roles in resistance to diabetes (GAPT4, ZNF608, and BBS2) (Nishimura et al, 2001;Speliotes et al, 2010), atherosclerosis (SERPINE1) (Koch et al, 2010), insulin secretion (UCP2) (Bordone et al, 2006), and energy expenditure (GPAM, PRKCA, and NCOA3) (Han et al, 2017;Yu et al, 2017).…”
Section: Bidirectional Selection In Bm and Durocmentioning
confidence: 99%
“…An increasing number of studies have shown that noncoding RNAs regulates various normal and pathological processes, such as microRNAs (miRNAs) [7][8][9][10] and long noncoding RNAs (lncRNAs) [11][12][13]. Although recent studies on the role of miRNAs and lncRNAs in adipogenesis have reached a mature stage, information on the functional roles of other classes of non-coding RNAs, such as circular RNAs (circRNAs) remains scanty.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have shown that non-coding RNAs regulates various normal and pathological processes, such as microRNAs (miRNAs) [7][8][9][10] and long non-coding RNAs (lncRNAs) [11][12][13]. Although recent studies on the role of miRNAs and lncRNAs in adipogenesis have reached a mature stage, information on the functional roles of other classes of non-coding RNAs, such as circular RNAs (circRNAs) remains scanty.…”
Section: Introductionmentioning
confidence: 99%